Comparison of the effects of linseed oil and different doses of fish oil on mononuclear cell function in healthy human subjects - Wallace, Fiona A.; Miles, Elizabeth A.; Calder, Philip C. (British journal of nutrition, 2003)
Studies on animal and human subjects have shown that greatly increasing the amount of linseed (also known as flaxseed) oil (rich in the n−3 polyunsaturated fatty acid (PUFA) α-linolenic acid (ALNA)) or fish oil (FO; rich in the long-chain n−3 PUFA eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) in the diet can decrease a number of markers of immune function. The immunological effects of more modest doses of n−3 PUFA in human subjects are unclear, dose–response relationships between n−3 PUFA supply and immune function have not been established and whether ALNA has the same effects as its long-chain derivatives is not known. Therefore, the objective of the present study was to determine the effect of enriching the diet with different doses of FO or with a modest dose of ALNA on a range of functional responses of human monocytes and lymphocytes. In a randomised, placebo-controlled, double-blind, parallel study, forty healthy males aged 18–39 years were randomised to receive placebo or 3·5 g ALNA/d or 0·44, 0·94 or 1·9 g (EPA+DHA)/d in capsules for 12 weeks. The EPA:DHA ratio in the FO used was 1·0:2·5. ALNA supplementation increased the proportion of EPA but not DHA in plasma phospholipids. FO supplementation decreased the proportions of linoleic acid and arachidonic acid and increased the proportions of EPA and DHA in plasma phospholipids. The interventions did not alter circulating mononuclear cell subsets or the production of tumour necrosis factor-α, interleukin (IL) 1β, IL-2, IL-4, IL-10 or interferon-γ by stimulated mononuclear cells. There was little effect of the interventions on lymphocyte proliferation. The two higher doses of FO resulted in a significant decrease in IL-6 production by stimulated mononuclear cells. It is concluded that, with the exception of IL-6 production, a modest increase in intake of either ALNA or EPA+DHA does not influence the functional activity of mononuclear cells. The threshold of EPA+DHA intake that results in decreased IL-6 production is between 0·44 and 0·94 g/d.